2016
DOI: 10.1177/0262728016663276
|View full text |Cite
|
Sign up to set email alerts
|

Lift Irrigation Schemes in Andhra Pradesh

Abstract: Despite efforts by the Indian state to develop and maintain various irrigation strategies, many projects have not achieved the desired results, often due to systemic problems inherent in these initiatives. Meanwhile, the growing scarcity of water in South Asia propels new thinking about remedies. Based on detailed fieldwork, this article, which seems at first completely unrelated to matters of caste discrimination, assesses the sustainability of lift irrigation schemes (LIS) in Andhra Pradesh (AP). Asking crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Fourth, India cannot equate herself with the LDCs of the world, given the scale and level of the country's economic growth and development. Fifth, since 2007, there has been a pragmatic shift in India's climate change policy and India is meanwhile doing reasonably well in setting up unilateral targets for mitigation of GHG emissions, particularly, after some earlier reluctance (Kalle & Kasi, 2016) by emphasising solar energy. On the opening day of the Paris Conference, Prime Minister Modi and the French President launched an International Solar Alliance (2015), inviting all countries located fully or partially between the Tropics of Cancer and Capricorn to boost solar energy in developing countries through joint efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, India cannot equate herself with the LDCs of the world, given the scale and level of the country's economic growth and development. Fifth, since 2007, there has been a pragmatic shift in India's climate change policy and India is meanwhile doing reasonably well in setting up unilateral targets for mitigation of GHG emissions, particularly, after some earlier reluctance (Kalle & Kasi, 2016) by emphasising solar energy. On the opening day of the Paris Conference, Prime Minister Modi and the French President launched an International Solar Alliance (2015), inviting all countries located fully or partially between the Tropics of Cancer and Capricorn to boost solar energy in developing countries through joint efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Tenure insecurity in turn leads to inferior investment incentives, undersupply of credit and constraints on efficiency-enhancing market exchanges (Reddy & Bantilan, 2013;Veettil et al, 2013). While it was earlier reported that land rights and titles to tribal land in India generally do not exist (Banerjee & Iyer, 2005;Mearns, 1999;Mearns & Sinha 1998), studies like Besley (1995), Besley et al (2016) and Kalle & Kasi (2016) showed that developing land rights can be a feasible intervention in the Global South.…”
Section: Global and National Debates On Tribal Land Rightsmentioning
confidence: 99%
“…This problem can easily be addressed by de-silting the tanks usually in the dry season. The second approach to rejuvenating poor functioning irrigation tanks, as Kalle and Kasi [28] note, is to supplement them with water from external sources. Through what is called a lift irrigation scheme (LIS), one could mechanically lift water from streams, rivers, or other water bodies using pump systems and push it to higher elevation and then distribute the same to various irrigation tanks in the command area.…”
Section: The Context Of This Studymentioning
confidence: 99%